Health-related quality of life among Ebola survivors in Sierra Leone: the role of socio-demographic, health-related and psycho-social factors - Peter Bai James; Jon Wardle; Razak M. Gyasi; Amie Steel; Jon Adams; John Alimamy Kabba; Abdulai Jawo Bah; Michael Lahai; Eugene B. Conteh (Health and Quality of Life Outcomes, 2022)
Abstract Background Evidence of how social factors affect the health-related quality of life (HRQoL) of Ebola virus disease (EVD) survivors is limited. Our study explores the association between socio-demographic, health-related and psycho-social (stigma) factors and EVD survivors' health-related quality of life (HRQoL) in Sierra Leone. Methods We conducted a nationwide cross-sectional study among 358 EVD survivors between January and August 2018. We used a multistage sampling method to recruit EVD survivors, and the RAND 36-Item Health Survey item was used to assess the HRQoL. Data were analysed using descriptive statistics and multiple linear regression. Results When comparing by each dimension in relation to their respective summary scores, role limitation physical [0.00 (50.00)] and role limitation emotional [0.00 (33.33)] were the most affected physical health and mental health domains among EVD survivors respectively. EVD survivors who were older (β = − 3.90, 95% CI − 6.47 to − 1.32, p = 0.003), had no formal education (β = − 2.80, 95% CI − 5.16 to − 0.43, p = 0.021), experienced a unit increase in the number of post-Ebola symptoms (β = − 1.08, 95% CI − 1.74 to − 0.43, p < 0.001) and experienced a unit increase in enacted stigma (β = − 2.61, 95% CI − 4.02 to − 1.20, p < 0.001) were more likely to report a decreased level of physical health. EVD survivors who experienced a unit increase in the time spent in the Ebola treatment centre (β = − 0.60, 95% CI − 0.103 to − 0.18, p = 0.006) and those who experienced a unit increase in enacted Stigma were more likely to report decreased levels of mental health (β = − 1.50, 95% CI − 2.67 to − 0.33, p = 0.012). Conclusion Sociodemographic, health-related, and psycho-social factors were significantly associated with decrease levels of HRQoL. Our findings improve our understanding of the factors that might influence the HRQoL and suggest the need for EVD survivors to be provided with a comprehensive healthcare package that caters for their physical and mental health needs.